2016
DOI: 10.1108/jmhtep-09-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Research based theatre in dementia knowledge transfer: views from the front line

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This type of intervention involves combining at least two self-experience practices to improve outcomes by combining the practices and/or providing a more comprehensive account of dementia. Four reports each described four different intervention programmes, all of which combined passive and interactive measures [ 43 , 59 , 65 , 83 ]. The passive components included films or short case vignettes [ 43 , 65 , 83 ], with one intervention programme incorporating a theatrical production [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of intervention involves combining at least two self-experience practices to improve outcomes by combining the practices and/or providing a more comprehensive account of dementia. Four reports each described four different intervention programmes, all of which combined passive and interactive measures [ 43 , 59 , 65 , 83 ]. The passive components included films or short case vignettes [ 43 , 65 , 83 ], with one intervention programme incorporating a theatrical production [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four reports each described four different intervention programmes, all of which combined passive and interactive measures [ 43 , 59 , 65 , 83 ]. The passive components included films or short case vignettes [ 43 , 65 , 83 ], with one intervention programme incorporating a theatrical production [ 59 ]. The interactive practices, which followed the passive practices in all cases, involved group exercises such as physical simulations [ 59 , 65 , 83 ] and/or role-plays [ 43 , 59 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, I found examples of successful theatrical dissemination from previous research. Argyle and Schneider (2016), who disseminated knowledge about dementia, reported that a performance like this was well received by attendees, who demonstrated high degrees of cognitive and emotional engagement, and that these positive reactions were sustained over time among the audience. Similarly, results from Gjengedal et al's (2018) project, which yielded insights into what it is like living close to persons with dementia (also using theatrical production), also provide evidence on the positive impact of theatre.…”
Section: Perceived Benefitsmentioning
confidence: 93%
“…It is apparent that theatrical performances for dissemination of results from health and social sciences have a wide spectrum. Evidence is found in different clinical specialties, in particular: neurodegenerative diseases (Argyle & Schneider, 2016;Gjengedal et al, 2018), cancer (Gray et al, 2003), contagious diseases (Bosompra, 2007), and (traumat-ic) injuries (Colantonio et al, 2008). Furthermore, patients' stories of receiving health care (Rosenbaum et al, 2005) can also be communicated through this medium.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, taking hospitals as example, there is evidence that dementia training based on the values of person centred care (Brooker and Latham, 2016) can have a positive impact on factors such as levels of confidence and dementia related knowledge of staff (Elvish et al (2016) and can positively impact on staff attitudes and a "sense of hope" (Surr et al, 2016). Similarly, Argyle and Schneider (2016) found evidence of "knowledge transfer" following an innovative theatre-based learning event, however the authors did not find evidence of this translating into changes to practice and highlighted the problem of the "implementation-gap" and posit that there are contextual barriers and facilitators to the utilisation of learning. This would accord with the findings of a systematic review by Livingston et al (2014) which found that person centred training for care home staff was only effective in reducing levels of agitation in residents when combined with ongoing "ongoing practical and theoretical advice in implementation, rather than initial training only " (p20, 2014).…”
Section: Introduction Introductionmentioning
confidence: 99%